Climate-Smart Villages: A community approach to sustainable agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
The CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS) has developed the Climate-Smart Village project in several regions in South Asia, East Africa and West Africa. Climate-Smart Villages are sites where local communities work with researchers, policymakers, scientists and NGOs to develop a strategic approach to sustainable agriculture through climate-smart agriculture practices and technologies. Climate-smart agriculture works to build farmers' resilience to climate change, increase their productivity and incomes, while mitigating greenhouse gas emissions from agriculture. A sustainable approach to agriculture is the future of a food secure planet. This film captures ongoing activities in Climate-Smart Villages in Bihar and Haryana in India. Learn more about Climate Smart Villages https://ccafs.cgiar.org/what-are-climate-smart-villages#.UvB2HT2SzzM